Analisis Penyelesaian Kepailitan Perbankan Syariah Di Pengadilan Niaga Dalam Putusan No.01/Pdt-Suspkpu/2015/Pn Niaga Medan Ditinjau Dari Perspektif Ekonomi Islam - Siti Kadariah; Pangeran Harahap; S Sukiati (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to explain the legal basis for bankruptcy settlement on musyarakah and murabahah financing in the Commercial Court in the decision No.01 / Pdt-Sus-PKPU / 2015 / PN Niaga Mdn, this study aims to explain whether in the decision No.01 / Pdt-Sus-PKPU / 2015 / PN Niaga Mdn is in accordance with sharia principles based on Islamic economic theory. The research method that will be used in this research is qualitative research methods that arefield research, namely detailed research on one particular subject, and one document. This research is a qualitative research obtained by compilers based on data in the field, namely in the Medan District Court, North Sumatra. The research approach used by the compiler is a normative approach, the normative approach is to approach the problem by seeing and seeing a discussion of a problem with emphasis on legal aspects Islam in this study is based on Islamic law which has been interpreted through the fatwa of the National Sharia Council (DSN), KHES, KHAES, andbooks Fiqh. The collection technique used by the author to collect research data is by using the interview method with Mr. Jamaluddin , SH, MH (Public Relations & Judges of the Medan District Court) and using the compiling documentation method to collect documents regarding sharia banking decision letters which were decided at the Medan District Court and other supporting documents.